2014
DOI: 10.1007/s00604-014-1407-2
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoclusters coated with bovine serum albumin as a regenerable fluorescent probe for copper(II) ion

Abstract: We show that copper nanoclusters coated with bovine serum albumin are viable probes for fluorometric determination of Cu(II) ion. The effect is attributed to the paramagnetic nature of Cu(II) bound to BSA. The ions Hg(II) and Fe(III) also give a strong effect but can be discerned by addition of EDTA. The probe can be regenerated by adding an excess of EDTA. The method is capable of detecting Cu(II) in the 0.02-34 μM, and the limit of detection is 1nM. The method was applied to the determination of Cu(II) in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The fluorescent metal NCs are promising probes due to their ultrafine size, good biocompatibility, low toxicity, excellent photostability and ease of synthesis [19]. Compared with the expensive precursors for the synthesis of Au-NCs and Ag-NCs, the precursor for the preparation of Cu-NCs is relatively abundant, inexpensive and readily available from commercial sources, therefore the fluorescent Cu-NCs are more favorable for the practical applications than the noble metal NCs [15]. Herein, we synthesized stable and highly fluorescent Cu-NCs through a facile one-step strategy using formaldehyde as the reductant and PVP as the protecting agent.…”
Section: Choice Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescent metal NCs are promising probes due to their ultrafine size, good biocompatibility, low toxicity, excellent photostability and ease of synthesis [19]. Compared with the expensive precursors for the synthesis of Au-NCs and Ag-NCs, the precursor for the preparation of Cu-NCs is relatively abundant, inexpensive and readily available from commercial sources, therefore the fluorescent Cu-NCs are more favorable for the practical applications than the noble metal NCs [15]. Herein, we synthesized stable and highly fluorescent Cu-NCs through a facile one-step strategy using formaldehyde as the reductant and PVP as the protecting agent.…”
Section: Choice Of Materialsmentioning
confidence: 99%
“…comparison to the fast increasing number of fluorescent AuNCs and Ag-NCs probes for the detection of various targets, analytical applications of fluorescent Cu-NCs are relatively limited [14,15]. To the authors' knowledge, no Cu-NCs based fluorescent probes have been reported for hypochlorite until now.…”
Section: Introductionmentioning
confidence: 97%
“…Zhong et al [23] found that the fluorescence of the BSA coated Cu NCs can be Li et al [24] developed a simple method for the detection of Cu 2+ by a FL turn-on strategy, which is based on the formation of red fluorescent Cu NCs with D-Penicillamine in ethanol media through solvent induced formation mechanism. By using ethanol to replace water as reaction media, the fluorescent Cu NCs were formed very quickly.…”
Section: Cu 2+ Sensormentioning
confidence: 99%
“…However, high cost of those noble metal nanoparticles largely limits their applications. Compared with noble metal nanostructures, copper is cheaper 55 than noble metals, which supports its wide range of applications such as catalysts [23][24][25] , sensors [26][27][28][29] and biomedicine 30, 31 . In a word, to improve the catalytic efficiency and reduce the costs, a cheap, simple and onestep preparation method of metal nanoparticles with peroxidaselike activity is highly desired.…”
Section: Introductionmentioning
confidence: 99%